2016
DOI: 10.1080/14397595.2016.1192745
|View full text |Cite
|
Sign up to set email alerts
|

Disease flare patterns and predictors of systemic lupus erythematosus in a monocentric cohort of 423 Japanese patients during a long-term follow-up: The JUDE study

Abstract: Thrombocytopenia at onset is predictive factor for flares. Since SLE is a diverse disease with varying symptoms at recurrence, the treatment guidelines should be improved for thrombocytopenia from a long-term perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…These differences may have been caused by the stringent inclusion criteria in the present study. However, the gender ratio and age distribution, with the exception of the elderly population, were similar to those described in previous studies …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These differences may have been caused by the stringent inclusion criteria in the present study. However, the gender ratio and age distribution, with the exception of the elderly population, were similar to those described in previous studies …”
Section: Discussionsupporting
confidence: 88%
“…The mean (SD) number of flares per patient was 5.5 (3.3) times over the 3‐year study period, which increased with SLE severity (ANOVA, P < 0.001). The proportion of patients experiencing a severe flare during the study (105 patients, 35.6%) was consistent with the proportion of patients (31.9%) reported in a long‐term follow‐up, monocentric SLE cohort . The mean costs per flare increased with SLE severity, consistent with results of a study that applied chart reviews and patient‐reported questionnaires in patients with SLE in Hong Kong .…”
Section: Discussionsupporting
confidence: 80%
“…Most of the patients (67.9%) experienced at least one disease flare within 10 years from diagnosis. This is in line with the JUDE study 26 that reported that in a Japanese cohort the majority of flares happened within the first 10 years from SLE onset, instead Swaak et al. in a multicentric study 18 found that 3-11% of patients had an exacerbation of disease during the last year of follow-up (median duration of SLE 16 years).…”
Section: Discussionsupporting
confidence: 85%
“…5 Moreover, a single-centre cohort study in Japan confirmed that thrombocytopaenia at onset was a predictive factor for flares and that treatment guidelines for thrombocytopaenia should be improved in the long term. 30 Both clinical practice and published studies suggested that thrombocytopaenia was associated with multiple organ damage in SLE. 25 In this study, univariate analysis showed that SLE patients with thrombocytopaenia had more severe clinical manifestations, including neurological manifestations, oral mucosal ulceration, pleurisy, pericarditis, hyperglycaemia, leucocytopaenia, urinary casts, haematuria and pyuria.…”
Section: Discussionmentioning
confidence: 99%